Comparative studies on tissue culture, morphologicaland antimicrobial properties of Clitoria ternatea L. and Onobrychis viciifolia Scop / Noraini Mahmad - Noraini , Mahmad (2017)
In the present study, tissue culture technique was used for Clitoria ternatea L. (tropical legume) and Onobrychis viciifolia Scop. (temperate legume) for comparison in plant regeneration by manipulation and exploitation of different temperatures (18, 24 and 30±1ºC), different concentrations of adenine hemisulfate (ADSO4), auxins (NAA and 2,4-D), cytokinins (BAP and KIN) and different explant sources (root, stem and flower bud). The best temperature for seeds germination for both species was at 24±1ºC, grown in vivo and in vitro. The optimum regeneration medium for C. ternatea L. was MS supplemented with 40.0 mg/L ADSO4, 2.0 mg/L NAA and 1.0 mg/L BAP which resulted in shoots (12.03±0.12) and roots (8.72±1.27) formation, whilst, the optimum medium for O. viciifolia Scop. was MS supplemented with 40.0 mg/L ADSO4, 1.0 mg/L 2,4-D and 3.0 mg/L KIN with formation of shoots (17.97±0.09) and roots (4.11±0.42). The optimum medium for synthetic seed production was obtained on MS medium supplemented with combinations of 40.0 mg/L ADSO4, 2.0 mg/L NAA and 1.0 mg/L BAP for C. ternatea L., while O. viciifolia Scop. on MS medium supplemented with 40.0 mg/L ADSO4, 1.0 mg/L NAA and 2.0 mg/L BAP, by using 3.0% (w/v) sodium alginate (NaC6H7O6) and soaked in 100 mM (w/v) calcium chloride dehydrate (CaCl2.2H2O) solution for 30 minutes. Synthetic seed production was initiated from embryogenic callus of both species and the seeds managed to survive for 3 months. All plantlets obtained were successfully acclimatized with 91.07±0.96% survival rate for C. ternatea L. and 71.58±1.27% survival rate for O. viciifolia Scop. Due to the importance of micromorphological features for the taxonomic consideration, FESEM and histology analysis revealed the presence of shallow pit of stomata and non-glandular trichomes with sharp-point end, the same as mother plant indicating no occurance of somaclonal variations. These species responded positively against bacteria (Bacillus subtilis, Staphylococcus aureus and Escherichia coli) and fungi (Fusarium sp., Candida albican and Trichoderma sp.). For potential use in paint technology, it was found that anthocyanin from vivid blue petals of C. ternatea L., was able to withstand pH, heat, UV and NaCl. Generally, the anthocyanin absorbance values of C. ternatea L. decreased when tested with higher pH, longer duration of UV radiation, higher concentrations of NaCl and longer exposure of heat (at 50±1ºC). The colour of this anthocyanin influenced by pH (red at pH 1, purple at pH 4.5, blue at pH 5.5 and cyan at pH 6.5) and became darker in the oven (at 50±1ºC) as the duration increased. The additional of 1% tartaric acid to anthocyanin-PMMA was found to be the best stabilizer to improve the colorant stability and durability. Overall, C. ternatea L. capable to adapt in both tropical and temperate regions without any geographical and seasonal constraints for year round commercial cultivation.